Cataloguing in the Digital Age - Ede, Stuart (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
Some fundamental changes are happening, or will have to happen, to adapt our catalogues to cope with what I call the Digital Age - an age in which we have to meet our users’ requirement to find the information they want irrespective of whether it is in print or digital form and whether it is held locally or on the Web. This is posing some huge challenges - indeed it is forcing a radical rethink of what libraries are for and what their role should be. The whole of the information world is at a crossroads. It is my belief that cataloguing in some form or other is still the key to access - indeed it is even more important if users are to find the knowledge and information they need amongst the tidal wave of raw data. However, cataloguing is an expensive business, and the economic pressures will be made worse by the increase in publishing in both digital and print formats. This will force the even wider re-use of records than is already occurring, but efficient re-use is only possible if records are prepared to common standards. A major focus of this paper is therefore the development of standards and the factors that will influence the direction that takes.